2016
DOI: 10.1177/0886260516683173
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity Mediates Relations Between Attachment and Aggression Differently by Gender

Abstract: The present study examined relations among attachment, aggression, and anxiety sensitivity (AS) in a sample of male and female undergraduates. Given that some individuals may use aggression to modulate negative emotional states, it was predicted that AS dimensions would mediate relations between attachment anxiety (vs. attachment avoidance) and certain forms of aggression, particularly impulsive aggression. Moreover, it was hypothesized that the relations among attachment, aggression, and AS would be moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…Although not based on I‐PACE, previous research across several domains (e.g. between emotional disorders and smoking [Zvolensky et al, 2014 ], attachment and aggression [Watt et al, 2020 ], and between anxiety/depression and opioid misuse [Rogers et al, 2020 ]) established AS as a mediator, suggesting AS may best be conceptualized as a mediating variable in the present study.…”
Section: Introductionmentioning
confidence: 55%
“…Although not based on I‐PACE, previous research across several domains (e.g. between emotional disorders and smoking [Zvolensky et al, 2014 ], attachment and aggression [Watt et al, 2020 ], and between anxiety/depression and opioid misuse [Rogers et al, 2020 ]) established AS as a mediator, suggesting AS may best be conceptualized as a mediating variable in the present study.…”
Section: Introductionmentioning
confidence: 55%
“…Previous research (Watt et al, 2016; You and Kim, 2016; McDermott et al, 2017; Nakamura and Kawabata, 2018) focused their attention on the difference between male and females in the relationship between attachment and aggression. Specifically, Nakamura and Kawabata (2018) underlined that anxiously attached males displayed higher levels of both proactive and reactive aggression than anxiously attached females, who showed only proactive aggression.…”
Section: Attachment To Parents and Peers And Aggressionmentioning
confidence: 99%
“…Moreover, You and Kim (2016), conducted a study of a sample of adolescents and found that females with higher levels of parent and peer attachment, higher levels of empathy and higher levels of self-control presented lower levels of aggression than males, whereas only peer attachment was negatively associated with aggression for males. Finally, Watt et al (2016) suggested that men report more attachment avoidance than women and higher levels of aggression.…”
Section: Attachment To Parents and Peers And Aggressionmentioning
confidence: 99%
“…Expression of anger is at the very core of emotional functioning of anxiously attached partners (e.g. Clear et al, 2019; Watt et al, 2017) and is likely to lead to a reactive conflict style. Moreover, hostile communication has been relatively strongly linked with relationship dissatisfaction in both sexes in Woodin’s (2011) meta-analysis.…”
Section: Discussionmentioning
confidence: 99%